Optimalisasi Penjualan Motor Menggunakan Algoritma Particle Swarm Optimization (PSO) - Juhardi, Ujang; Andilala, Andilala (UNIVED Press, 2019)
Currently there are still a lot of transportation users, the vehicles needed to meet daily needs never run out, many companies are competing in the transportation sector, especially in the field of motorbike sales. The research that will be carried out is to find out the results of increasing motorbike sales, to help speed up the process of optimizing increased sales using the Particle Swarm Optimization (PSO) algorithm. The conclusion of this research is to find out the discounts and down payments that will be used with the aim of increasing future motorbike sales and the estimated total sales over the next 12 months.